Familial cancer variant prioritization pipeline version 2 (FCVPPv2) applied to a papillary thyroid cancer family - Kumar, Abhishek; Bandapalli, Obul Reddy; Paramasivam, Nagarajan; Giangiobbe, Sara; Diquigiovanni, Chiara; Bonora, Elena; Eils, Roland; Schlesner, Matthias; Hemminki, Kari; Försti, Asta (Scientific reports, 2018)
Whole-genome sequencing methods in familial cancer are useful to unravel rare clinically important cancer predisposing variants. Here, we present improvements in our pedigree-based familial cancer variant prioritization pipeline referred as FCVPPv2, including 12 tools for evaluating deleteriousness and 5 intolerance scores for missense variants. This pipeline is also capable of assessing non-coding regions by combining FANTOM5 data with sets of tools like Bedtools, ChromHMM, Miranda, SNPnexus and Targetscan. We tested this pipeline in a family with history of a papillary thyroid cancer. Only one variant causing an amino acid change G573R (dbSNP ID rs145736623, NM_019609.4:exon11:c.G1717A:p.G573R) in the carboxypeptidase gene CPXM1 survived our pipeline. This variant is located in a highly conserved region across vertebrates in the peptidase_M14 domain (Pfam ID PF00246). The CPXM1 gene may be involved in adipogenesis and extracellular matrix remodelling and it has been suggested to be a tumour suppressor in breast cancer. However, the presence of the variant in the ExAC database suggests it to be a rare polymorphism or a low-penetrance risk allele. Overall, our pipeline is a comprehensive approach for prediction of predisposing variants for high-risk cancer families, for which a functional characterization is a crucial step to confirm their role in cancer predisposition.